2016
DOI: 10.1257/mac.20140362
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange Rate Response to Monetary Policy Innovations

Abstract: We present a new data fact: in response to a monetary tightening, the nominal exchange tends to appreciate in developed countries but depreciate in developing countries. A model is formalized to rationalize this contrasting pattern. It has three key channels of monetary transmission: a liquidity demand channel, a …scal channel and an output channel. These have o¤setting e¤ects on the exchange rate.The paper shows that a calibrated version of the model can explain the contrast between developed and developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
9
26
1
4
Order By: Relevance
“…Following an increase in the short-term interest rates relative to the US interest rate, the exchange rate volatility (filtered series) may increase due to a flow of funds into the exchange rate market. This finding was consistent with the Mundell-Fleming (M-F) model and in line with [2,5,8,17]. The IRFs implied that contractionary monetary policy implementations in these countries may lead to a deterioration in stability in currency markets and also other financial markets, which, in turn, may negatively affect the foreign competiveness of these countries and deteriorate real economic activity.…”
Section: Impulse Response Analysis Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Following an increase in the short-term interest rates relative to the US interest rate, the exchange rate volatility (filtered series) may increase due to a flow of funds into the exchange rate market. This finding was consistent with the Mundell-Fleming (M-F) model and in line with [2,5,8,17]. The IRFs implied that contractionary monetary policy implementations in these countries may lead to a deterioration in stability in currency markets and also other financial markets, which, in turn, may negatively affect the foreign competiveness of these countries and deteriorate real economic activity.…”
Section: Impulse Response Analysis Resultssupporting
confidence: 85%
“…When the scientific literature is examined, it has been recognised that VAR-type of models can be adopted to examine the impacts of monetary policy shocks on exchange rates. For instance, [8] found that the effect of a positive innovation in monetary policy is associated with an exchange rate appreciation in developed economies; it leads to significant depreciation in currencies of developing economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding presents critical challenges for academics and policymakers alike because of the inconsistency between theory and empirical evidence. Hnatkovska et al () intepret this finding as evidence of differential transmission mechanisms for monetary policy.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similar to Hnatkovska et al (2016), Cormun and Leo (2017) investigate the effects of shocks to US monetary policy on the value of currencies of other countries. Their findings confirm that when the US economic outlook worsens, developing countries' currencies significantly decline in value while their policycontrolled interest rates increase.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…Bjørnland (2009) argues that since exchange rate is an asset price, it should immediately respond to monetary policy shocks, possibly reflecting the news contained in the policy. Furthermore, event studies such as Zettelmeyer (2004) and Hnatkovska et al (2016) find significant contemporaneous responses of the exchange rate to a monetary policy shock in a range of countries.…”
Section: Introductionmentioning
confidence: 99%